2014
DOI: 10.1016/j.protis.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and Phylogenetic Position of a Warm-stenotherm Centric Diatom, Skeletonema potamos (C.I. Weber) Hasle and its Long-term Dynamics in the River Danube

Abstract: 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 3 IntroductionThe classic taxonomy of diatoms is morphology-based using features of their characteristic silica cell wall called frustule (e.g. Ettl et al. 1986). Medlin et al. (1988) introduced molecular methods into diatom taxonomy. Based on molecular, morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…To our knowledge, studies using modeling approaches for predicting areas susceptible to phytoplankton invasions are virtually nonexistent as most of the studies in this field are descriptive, although with good predictions (e.g., Cylindrospermopsis raciborskii , Prymnesium parvum , Skeletonema potamos ; Padisák , Duleba et al. , Roelke et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, studies using modeling approaches for predicting areas susceptible to phytoplankton invasions are virtually nonexistent as most of the studies in this field are descriptive, although with good predictions (e.g., Cylindrospermopsis raciborskii , Prymnesium parvum , Skeletonema potamos ; Padisák , Duleba et al. , Roelke et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that the characteristic dominance of eutrophic centric diatoms (codon D ) declined in the middle Danube in almost all seasons, except summer. This might be explained by the increasing summer dominance of the stenotherm Skeletonema potamos at this river section (Duleba et al., ). The species is highly adapted to extreme late summer river conditions: increased water temperature, elongated water residence time and high light availability (Kiss et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…Further details about the sampling can be found in Duleba et al. (); about the entire Danube basin in Sommerwerk et al. () and Liska ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations